Gold Price Forecasting Using Autoregressive Integrated Moving Average (ARIMA) Method - Ruth Elizabeth; Sitorus , Syahriol (Journal of Mathematics Technology and Education, 2021)
Gold is one type of investment that is starting to be favored by many people. Every investment has risk, including gold investment. This risk of loss needs to be minimized to obtain maximum profit. So it takes proper planning and forecasting to invest in gold. This study aims to determine the best forecasting model for the price of 1 gram gold bullion produced by PT Aneka Tambang (ANTAM), using the ARIMA method. The data used in this study comes from historical data in 2016 to 2019 to predict gold prices in 2020-2021. Gold Price Forecasting using the ARIMA method produces ARIMA(1,1,0) with the model model . . With error values ​​MAE= 94491.42, MAPE= 10.47776409, MSE= 12281027973, RMSE=110819.7996.